Relationship Between the Counselor's Personal Characteristics and Self-Development Experience with Individual Counseling Skills - Anne Hafina (Indonesian Journal of Community and Special Needs Education, 2024)
This research aims to see the relationship between the personal characteristics of the counselor with his counseling skills, the relationship between the counselor's self-development and counseling skills, Counselor's characteristic tendencies, Counselor's self-development tendency after working as a counselor in school. Data collection was carried out by distributing questionnaires to school counselors who served in high schools only, the sample was determined by stratified purposive sampling from 4 areas of the city of Bandung, Indonesia (north, south, west, and east). The calculation results yield 52 school counselors from 11 schools and 52 students who have become their clients. The results of the study show the relationship between personal characteristics and counseling skills shows a high and significant relationship and the relationship between self-development experience and counseling skills shows a high and significant relationship. The tendency of the counselor's characteristics is shown by the average score on each aspect that is disclosed the average score on each aspect shows the relationship between a counselor's characteristics and counseling skills has a high and significant relationship.